Chelating agent modified biochar / MOF materials and electrochemical sensors
By synthesizing MOFs materials in situ on the surface of biochar and grafting the chelating agent, the problem of insufficient sensitivity of biochar-based electrochemical sensors to Pb ion detection in water bodies is solved, and the effect of trace detection is achieved.
Patent Information
- Application Number
- CN202411526292.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Existing biochar-based electrochemical sensors cannot effectively detect Pb ions in water, and the detection sensitivity is low and cannot meet the requirements of trace detection.
The chelating agent is grafted on the surface of the composite material by synthesizing MOFs materials in situ on the surface of biochar and grafting the chelating agent on the surface of the composite material by using the chemical reaction between -NH2 in the MOFs materials and -COOH in the chelating agent to improve the electrochemical detection performance.
It significantly improves the electrochemical detection performance of composite materials, realizes trace detection of Pb ions in water, and meets the detection needs of high sensitivity.
Smart Images

Figure CN119039607B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical sensors and relates to chelating agent-modified biochar / MOF materials and electrochemical sensors. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Electrochemical sensors have attracted much attention due to their inherent advantages such as simple operation, fast response time, high cost-effectiveness, and real-time monitoring. The main factor affecting the detection performance of electrochemical sensors is the electrode material. The electrode material used as an electrochemical sensor should have rich pore structure and good conductivity.
[0004] Metal-organic framework materials (MOFs) have an ordered pore structure and a large specific surface area, and are a potential porous material for preparing electrochemical sensors. However, MOFs materials are semiconductor materials with limited conductivity. In order to enhance the intensity of the current signal during the detection process and improve the overall performance of the electrochemical sensor, it is an effective method to prepare composite materials by compounding MOFs materials with carbon materials with good conductivity. Biochar (BC) is a carbon material with a porous structure obtained by high-temperature pyrolysis of biomass materials under oxygen-limited conditions. Biochar has important applications in many fields due to its porous structure, rich functional groups on the surface, and good conductivity. However, the current strategies for composite materials are mostly to synthesize MOFs and carbon materials separately, and then load MOFs onto the surface of carbon materials by physical means such as ultrasound and stirring. However, the surface of carbon materials usually carries a negative charge, and the presence of organic ligands in MOFs materials usually causes the material to carry a negative charge. Therefore, problems such as low loading efficiency and easy agglomeration of MOFs materials often occur during the loading process, which affects the detection ability of electrochemical sensors prepared by biochar / MOFs. In particular, the detection sensitivity of Pb (lead) ions in water bodies is low and cannot meet the requirements of trace detection.
[0005] Therefore, it is urgent to solve the problem that biochar-based electrochemical sensors cannot detect trace amounts of Pb ions in water. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a chelating agent modified biochar / MOF material and an electrochemical sensor. The present invention makes full use of the porous characteristics of biochar. First, biochar is used to adsorb metal ions so that the metal ions are fully distributed on the surface of biochar. Then, the biochar adsorbed with metal ions is immersed in a solution containing organic ligands, so that the organic ligands and the metal ions adsorbed on the surface of the carbon material are coordinated to generate MOFs materials. Finally, the chelating agent is grafted on the surface of the composite material by the chemical reaction between -NH2 (amino group) in the MOFs material and -COOH (carboxyl group) in the chelating agent, and the electrochemical detection performance of the composite material is further improved by the complexation between the chelating agent and the metal ions. The present invention significantly improves the electrochemical detection performance of the composite material by combining the in-situ synthesis of MOFs on the biochar surface and the chelating agent modification strategy. The prepared electrochemical sensor can realize the trace detection of Pb ions in water.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The first aspect of the present invention provides a chelating agent-modified biochar / MOF material, which is prepared by the following method:
[0009] Adding hydrogen peroxide to the biochar dispersion to carry out a hydrothermal reaction, and after the reaction is completed, performing solid-liquid separation, washing, and drying to obtain modified biochar;
[0010] Dispersing the modified biochar in a phosphoric acid solution, heating it, and adding phosphorus pentoxide to react to obtain a phosphate-modified biochar;
[0011] Loading zirconium salt on the phosphate-modified biochar to obtain biochar loaded with zirconium ions;
[0012] The biochar loaded with zirconium ions is mixed with 2-aminoterephthalic acid, and a solvent thermal reaction is carried out in the presence of acetic acid. After the reaction is completed, solid-liquid separation, washing, and drying are performed to obtain NH2-UIO-66 (zirconium-based metal organic framework) / biochar composite material;
[0013] The diethylenetriaminepentaacetic acid aqueous solution is adjusted to acidity, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added for activation. After the activation is completed, the NH2-UIO-66 / biochar composite material is added for reaction. After the reaction is completed, the material is washed and dried to obtain a chelating agent-modified biochar / MOF material.
[0014] The present invention, based on the in-situ synthesis of a composite material with high loading rate and high dispersibility, further grafts a metal ion chelating agent on the surface of the material by technical means, thereby improving the electrochemical detection capability of the material.
[0015] The surface modification of biochar using hydrogen peroxide can improve its pore structure and specific surface area, increase the content of oxygen elements and oxygen-containing functional groups on the surface of biochar, and facilitate the subsequent modification of phosphate groups and the improvement of adsorption performance. In order to improve the modification effect of hydrogen peroxide on biochar, the present invention studies the conditions of the hydrothermal reaction. Preferably, the conditions of the hydrothermal reaction are 80°C-85°C for 4-5 hours.
[0016] After phosphoric acid modification, the surface of biochar contains a large number of functional groups such as hydroxyl and carboxyl, thereby increasing its chemical activity and facilitating the subsequent in-situ generation of MOFs. In order to increase the phosphorus content on biochar, the present invention studies the amount of phosphorus pentoxide. Preferably, the mass ratio of biochar to phosphorus pentoxide is 1:50-100, so as to load sufficient phosphate groups on the biochar.
[0017] The present application does not specifically limit the method of loading zirconium salt on biochar. Preferably, the specific steps of loading zirconium salt include: adding zirconium salt to the phosphate-modified biochar dispersion and stirring for 60-80 minutes. The above method has high zirconium ion loading efficiency and is simple.
[0018] The rigid structure of NH2-UIO-66 is a good catalyst carrier, which is composed of zirconium salt and 2-aminoterephthalic acid. During the synthesis, acetic acid is often added to catalyze the reaction process. If the amount of zirconium salt is small, the loading rate of zirconium ions on biochar is low, but after the amount of zirconium salt reaches a certain value, continuing to increase the amount of zirconium salt will not increase the loading rate of zirconium ions on biochar. Therefore, preferably, the mass ratio of the phosphate-modified biochar to the zirconium salt is 1-4:50-90.
[0019] Preferably, the zirconium salt is zirconium chloride.
[0020] In order to synthesize MOFs in situ on the surface of biochar, the present invention studies the dosage of 2-aminoterephthalic acid. Preferably, the mass ratio of the biochar loaded with zirconium ions to 2-aminoterephthalic acid is 5:78-80.
[0021] The progress of the solvothermal reaction can be regulated by changing the temperature and time. Therefore, the temperature and time of the solvothermal reaction are studied in the present invention. Preferably, the solvothermal reaction is carried out at 80° C.-85° C. for 18-20 hours.
[0022] In order to graft the chelating agent onto the surface of the NH2-UIO-66 / biochar composite material to improve its electrochemical detection performance, the present invention studies the dosage of diethylenetriaminepentaacetic acid. Preferably, the mass ratio of the NH2-UIO-66 / biochar composite material to diethylenetriaminepentaacetic acid is 3:60-70.
[0023] A second aspect of the present invention provides an electrochemical sensor, comprising: an electrochemical sensing electrode;
[0024] The electrochemical sensor electrode is prepared by the following method:
[0025] Dispersing the above-mentioned chelating agent-modified biochar / MOF material in a solvent to obtain a dispersion of the chelating agent-modified biochar / MOF material;
[0026] The dispersion of the chelating agent-modified biochar / MOF material is loaded on a glassy carbon electrode and dried to obtain the product.
[0027] Beneficial Effects of the Invention
[0028] (1) The present invention makes full use of the porous characteristics of biochar. First, biochar is used to adsorb metal ions so that the metal ions are fully distributed on the surface of biochar. Then, the biochar adsorbed with metal ions is immersed in a solution containing organic ligands, so that the organic ligands and the metal ions adsorbed on the surface of the carbon material are coordinated to form MOFs materials. Finally, the chelating agent is grafted on the surface of the composite material by the chemical reaction between -NH2 in the MOFs material and -COOH in the chelating agent, and the electrochemical detection performance of the composite material is further improved by the complexation between the chelating agent and the metal ions. The present invention significantly improves the electrochemical detection performance of the composite material by combining the in-situ synthesis of MOFs on the biochar surface and the chelating agent modification strategy. The prepared electrochemical sensor can realize trace detection of Pb ions in water.
[0029] (2) The present invention uses phosphate-modified biochar to fix zirconium ions by chemical adsorption, thereby improving the stability of MOFs on the surface of carbon materials;
[0030] (3) The present invention synthesizes NH2-UIO-66 material in situ on the surface of biochar, and the NH2-UIO-66 material has a high loading rate and good dispersibility on the surface of biochar;
[0031] (4) The present invention grafts a chelating agent (diethylenetriaminepentaacetic acid, abbreviated as DTPA) on the surface of the composite material through a chemical reaction, thereby further improving the electrode material's ability to enrich metal ions.
[0032] (5) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0034] Figure 1 This is the preparation route of the DTPA-modified NH2-UIO-66 / biochar composite material of the present invention.
[0035] Figure 2 Transmission electron microscope (a) and scanning electron microscope (b) images of the NH2-UIO-66 / biochar composite material prepared in situ in Example 1 of the present invention.
[0036] Figure 3 This is a linear relationship diagram of the detection of Pb ions in water by the DTPA-modified NH2-UIO-66 / biochar composite material in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0038] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0039] The raw materials described in the examples and comparative examples are all conventional raw materials and commercially available products.
[0040] Example 1
[0041] 1. Pretreatment of biochar materials:
[0042] 40 mg of biochar material was dispersed in 140 mL of DMF (N,N-dimethylformamide), ultrasonically dispersed, 7 mL of 30% hydrogen peroxide was added to the above solution, hydrothermal at 80°C for 5 hours, then centrifuged, washed with water, and dried. Then 40 mg of the above-treated biochar was dispersed in 150 mL of 85% concentrated phosphoric acid solution, heated to 50°C, and then 2 g of phosphorus pentoxide was added, kept warm for 3 hours, centrifuged, washed with water, and dried to obtain phosphate-modified biochar.
[0043] 2. In situ synthesis of MOFs (NH2-UIO-66) / biochar composites
[0044] First, 30 mg of phosphate-modified biochar was dispersed in 90 mL DMF and ultrasonically dispersed for 30 minutes to obtain a uniform dispersed solution. Subsequently, 750 mg of ZrCl4 (zirconium chloride) was added and magnetically stirred for 60 minutes to fully dissolve ZrCl4 and adsorb on the surface of biochar. The above solution was then centrifuged, washed three times with water, and dried at 80 °C to obtain biochar adsorbing zirconium ions. 390 mg of 2-aminoterephthalic acid was added to 50 mL DMF to prepare a uniform solution, and then 25 mg of the above biochar adsorbing zirconium ions was added and magnetically stirred for 20 minutes. Finally, 3.38 mL of acetic acid was added to the above solution, transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave reactor, and reacted at 80 °C for 20 hours. After the reaction was completed, centrifuged, washed, and dried to obtain NH2-UIO-66 / biochar composite material.
[0045] 3. Preparation of NH2-UIO-66 / biochar composites modified with chelating agent (DTPA)
[0046] 0.70 g DTPA was dissolved in 15 g pure water, and the pH of the solution was adjusted to 6.3 with NaOH (sodium hydroxide), and then 0.15 g EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide) and 0.3 g NHS (:N-hydroxysuccinimide) were quickly added. The resulting mixture was magnetically stirred at room temperature for 1 hour to activate the carboxyl groups of DTPA. Subsequently, the pH of the solution was adjusted to 7.2, and 30 mg NH2-UIO-66 / biochar composite was added. The resulting mixture was magnetically stirred at room temperature for 24 hours. Subsequently, the mixture was centrifuged and washed three times with ultrapure water to remove any remaining DTPA, EDC and NHS. Finally, it was dried in vacuum at 60 °C to obtain DTPA-modified NH2-UIO-66 / biochar composite powder.
[0047] 4. Characterization of NH2-UIO-66 / biochar composites modified with chelating agent (DTPA)
[0048] The preparation routes of the above materials are as follows Figure 1 The transmission electron microscopy of the material prepared in Example 1 is shown in Figure 2 As shown in (a), the scanning electron microscope photo is as follows Figure 2 As shown in (b), it can be seen that the MOFs material in the composite material prepared by the method of the present invention can be evenly dispersed on the surface of the carbon material, and the loading amount is relatively large.
[0049] 5. Performance test of NH2-UIO-66 / biochar composite modified by chelating agent (DTPA)
[0050] 10 mg of the synthesized DTPA-modified NH2-UIO-66 / biochar material was dispersed in 10 ml of ethanol and ultrasonicated to obtain a uniform dispersion. 20 μL of the dispersion was dropped on a polished glassy carbon electrode (GCE) and dried under an infrared lamp to prepare an electrochemical sensing electrode.
[0051] Anodic stripping voltammetry was used to detect trace amounts of Pb in water using a Chenhua CHI760E electrochemical workstation to evaluate the electrochemical properties of the prepared materials. The specific test conditions are as follows: All electrochemical measurements were performed using a three-electrode system, with Ag / AgCl (silver / silver chloride) electrodes and Pt (platinum) electrodes as reference electrodes and counter electrodes, respectively, and the sensing electrode as the working electrode. Heavy metal ions were dissolved in acetic acid and sodium acetate buffer solution (HAc-NaAc, pH = 5) to prepare a series of solutions with concentrations ranging from 0.1μM to 35μM for electrochemical testing.
[0052] The prepared sensing electrode has good detection performance for lead ions, cadmium ions and copper ions. The present invention takes the detection effect of lead as an example to demonstrate. Figure 3 The linear relationship of the DTPA-modified NH2-UIO-66 / biochar composite material prepared in Example 1 for detecting Pb ions in water bodies shows that the linear range of the material prepared by the present invention for detecting Pb ions in water buckets can be from 0.01 μM to 35 μM. The linear regression equation can be obtained within the concentration range as y=13.002x-0.045, the correlation coefficient is 0.9899, and the detection limit is 0.004 μM.
[0053] Example 2
[0054] 1. Pretreatment of biochar materials:
[0055] 40 mg of biochar material was dispersed in 140 mL of DMF and dispersed by ultrasonic. 10 mL of 30% hydrogen peroxide was added to the above solution, and the mixture was heated at 80°C for 5 hours, then centrifuged, washed, and dried. Then 40 mg of the above-treated biochar was dispersed in 150 mL of 85% concentrated phosphoric acid solution, heated to 50°C, and then 3 g of phosphorus pentoxide was added. The mixture was kept warm for 3 hours, centrifuged, washed, and dried to obtain phosphate-modified biochar.
[0056] 2. In situ synthesis of MOFs (NH2-UIO-66) / biochar composites
[0057] First, 40 mg of phosphate-modified biochar was dispersed in 90 mL DMF and ultrasonically dispersed for 30 minutes to obtain a uniform dispersed solution. Subsequently, 900 mg of ZrCl4 was added and magnetically stirred for 80 minutes to fully dissolve ZrCl4 and adsorb on the surface of biochar. The above solution was then centrifuged, washed three times with water, and dried at 80°C to obtain biochar adsorbing zirconium ions. 390 mg of 2-aminoterephthalic acid was added to 50 mL DMF to prepare a uniform solution, and then 25 mg of the above biochar adsorbing zirconium ions was added and magnetically stirred for 20 minutes. Finally, 3.38 mL of acetic acid was added to the above solution, transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave reactor, and reacted at 80°C for 20 hours. After the reaction was completed, centrifuged, washed, and dried to obtain NH2-UIO-66 / biochar composite material.
[0058] 3. Preparation of NH2-UIO-66 / biochar composites modified with chelating agent (DTPA)
[0059] 0.70 g DTPA was dissolved in 15 g pure water, and the pH of the solution was adjusted to 6.3 with NaOH, and then 0.15 g EDC and 0.3 g NHS were quickly added. The resulting mixture was magnetically stirred at room temperature for 1 hour to activate the carboxyl groups of DTPA. Subsequently, the pH of the solution was adjusted to 7.2, and 30 mg NH2-UIO-66 / biochar composite was added. The resulting mixture was magnetically stirred at room temperature for 24 hours. Subsequently, the mixture was centrifuged and washed three times with ultrapure water to remove any remaining DTPA, EDC, and NHS. Finally, the DTPA-modified NH2-UIO-66 / biochar composite powder was obtained by vacuum drying at 60 °C.
[0060] The same detection method as in Example 1 was used to detect the performance of the material prepared in Example 2. The linear range was from 0.01 μM to 35 μM. Within the concentration range, the linear regression equation was y=11.472x-0.029, the correlation coefficient was 0.9952, and the detection limit was 0.004 μM.
[0061] Example 3
[0062] 1. Pretreatment of biochar materials:
[0063] 40 mg of biochar material was dispersed in 140 mL of DMF and dispersed by ultrasound. 5 mL of 30% hydrogen peroxide was added to the above solution, and the mixture was heated at 85°C for 4 hours, then centrifuged, washed, and dried. Then 40 mg of the above-treated biochar was dispersed in 150 mL of 85% concentrated phosphoric acid solution, heated to 50°C, and then 4 g of phosphorus pentoxide was added. The mixture was kept warm for 3 hours, centrifuged, washed, and dried to obtain phosphate-modified biochar.
[0064] 2. In situ synthesis of MOFs (NH2-UIO-66) / biochar composites
[0065] First, 10 mg of phosphate-modified biochar was dispersed in 90 mL DMF and ultrasonically dispersed for 30 minutes to obtain a uniform dispersed solution. Subsequently, 500 mg of ZrCl4 was added and magnetically stirred for 60 minutes to fully dissolve ZrCl4 and adsorb on the surface of biochar. The above solution was then centrifuged, washed three times with water, and dried at 80°C to obtain biochar adsorbing zirconium ions. 400 mg of 2-aminoterephthalic acid was added to 50 mL DMF to prepare a uniform solution, and then 25 mg of the above biochar adsorbing zirconium ions was added and magnetically stirred for 20 minutes. Finally, 3.38 mL of acetic acid was added to the above solution, transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave reactor, and reacted at 85°C for 18 hours. After the reaction was completed, centrifuged, washed, and dried to obtain NH2-UIO-66 / biochar composite material.
[0066] 3. Preparation of NH2-UIO-66 / biochar composites modified with chelating agent (DTPA)
[0067] 0.60 g DTPA was dissolved in 15 g pure water, and the pH of the solution was adjusted to 6.3 with NaOH, and then 0.15 g EDC and 0.3 g NHS were quickly added. The resulting mixture was magnetically stirred at room temperature for 1 hour to activate the carboxyl groups of DTPA. Subsequently, the pH of the solution was adjusted to 7.2, and 30 mg NH2-UIO-66 / biochar composite was added. The resulting mixture was magnetically stirred at room temperature for 24 hours. Subsequently, the mixture was centrifuged and washed three times with ultrapure water to remove any remaining DTPA, EDC, and NHS. Finally, the DTPA-modified NH2-UIO-66 / biochar composite powder was obtained by vacuum drying at 60 °C.
[0068] The same detection method as in Example 1 was used to detect the performance of the material prepared in Example 2. The linear range was from 0.01 μM to 35 μM. Within the concentration range, the linear regression equation was y=12.292x-0.018, the correlation coefficient was 0.9910, and the detection limit was 0.004 μM.
[0069] Comparative Example 1
[0070] The difference from Example 1 is that the chelating agent is directly loaded on MOFs (NH2-UIO-66).
[0071] The same detection method as in Example 1 was used to detect the performance of the material prepared in Comparative Example 1. The linear range was from 0.1 μM to 35 μM. Within the concentration range, the linear regression equation was y=2.578x-0.080, the correlation coefficient was 0.9850, and the detection limit was 0.01 μM.
[0072] Comparative Example 2
[0073] The difference from Example 1 is that no chelating agent is loaded.
[0074] The same detection method as in Example 1 was used to detect the performance of the material prepared in Comparative Example 2. The linear range was from 0.5 μM to 35 μM. Within the concentration range, the linear regression equation was y = 2.453x - 0.204, the correlation coefficient was 0.9890, and the detection limit was 0.05 μM.
[0075] From the comparison between Example 1 and Comparative Examples 1 and 2, it can be seen that the present invention significantly improves the electrochemical detection performance of the composite material through the combination of in situ synthesis of MOFs on the biochar surface and chelating agent (DTPA) modification strategy, and realizes trace detection of Pb ions in water.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A chelating agent modified biochar / MOF material, characterized in that: Prepared by the following method: Adding hydrogen peroxide to the biochar dispersion to carry out a hydrothermal reaction, and after the reaction is completed, performing solid-liquid separation, washing, and drying to obtain modified biochar; Dispersing the modified biochar in a phosphoric acid solution, heating it, and adding phosphorus pentoxide to react to obtain a phosphate-modified biochar; Loading zirconium salt on the phosphate-modified biochar to obtain biochar loaded with zirconium ions; The biochar loaded with zirconium ions is mixed with 2-aminoterephthalic acid, and a solvent thermal reaction is carried out in the presence of acetic acid. After the reaction is completed, solid-liquid separation, washing, and drying are performed to obtain an NH2-UIO-66 / biochar composite material; The diethylenetriaminepentaacetic acid aqueous solution is adjusted to acidity, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added for activation. After the activation is completed, the NH2-UIO-66 / biochar composite material is added for reaction. After the reaction is completed, the material is washed and dried to obtain a chelating agent-modified biochar / MOF material.
2. The chelating agent-modified biochar / MOF material according to claim 1, characterized in that: The hydrothermal reaction is carried out at 80°C-85°C for 4-5 hours.
3. The chelating agent-modified biochar / MOF material according to claim 1, characterized in that: The mass ratio of the biochar to phosphorus pentoxide is 1:50-100.
4. The chelating agent-modified biochar / MOF material according to claim 1, characterized in that: The specific steps of loading the zirconium salt include: adding the zirconium salt to the phosphate-modified biochar dispersion, and stirring for 60-80 minutes.
5. The chelating agent-modified biochar / MOF material according to claim 1, characterized in that: The mass ratio of the phosphate-modified biochar to the zirconium salt is 1-4:50-90.
6. The chelating agent-modified biochar / MOF material according to claim 5, characterized in that: The zirconium salt is zirconium chloride.
7. The chelating agent-modified biochar / MOF material according to claim 1, characterized in that: The mass ratio of the biochar loaded with zirconium ions to 2-aminoterephthalic acid is 5:78-80.
8. The chelating agent-modified biochar / MOF material according to claim 1, characterized in that: The solvent thermal reaction conditions are 80° C.-85° C. for 18-20 hours.
9. The chelating agent-modified biochar / MOF material according to claim 1, characterized in that: The mass ratio of the NH2-UIO-66 / biochar composite material to diethylenetriaminepentaacetic acid is 3:60-70.
10. An electrochemical sensor, characterized in that: include: Electrochemical sensing electrodes; The electrochemical sensor electrode is prepared by the following method: Dispersing the chelating agent modified biochar / MOF material according to any one of claims 1 to 8 in a solvent to obtain a dispersion of the chelating agent modified biochar / MOF material; The dispersion of the chelating agent-modified biochar / MOF material is loaded on a glassy carbon electrode and dried to obtain the product.
Citation Information
Patent Citations
Method of using hydrogen peroxide and phosphoric acid to modify active carbon electrode material
CN110510610A
Preparation method of graphene-based composite aerogel material for adsorbing heavy metal ions
CN117920155A